Systematic studies of Anopheles (Cellia) kochi (Diptera: Culicidae): Morphology, cytogenetics, cross-mating experiments, molecular evidence and susceptibility level to infection with nocturnally subperiodic Brugia malayi - Watchara Jatuwattana (2020)
© 2019 Elsevier B.V. Anopheles kochi Dӧnitz (Diptera: Culicidae) is a malaria vector in some countries in South and Southeast Asia. This is the first report to provide clear evidence that two different cytological forms of An. kochi are conspecific based on systematic studies. Two karyotypic forms, i.e., Form A (X1, X2, Y1) and a novel Form B (X1, X2, Y2) were obtained from a total of 15 iso-female lines collected from five provinces in Thailand. Form A was common in all provinces, whereas Form B was restricted to Ubon Ratchathani province. This study determined whether the two karyotypic variants of An. kochi exist as a single or cryptic species by performing cross-mating experiments in association with the sequencing of the second internal transcribed spacer (ITS2) of ribosomal DNA (rDNA), and cytochrome c oxidase subunit I (COI) of mitochondrial DNA (mtDNA). Cross-mating experiments between the two karyotypic forms revealed genetic compatibility by providing viable progenies through F2 generations. The two forms showed a high sequence similarity of those two DNA regions (average genetic distances: ITS2 = 0.002–0.005, COI = 0.000–0.009). The phylogenetic trees based on ITS2 and COI sequences also supported that four strains (from Bhutan, Cambodia, Indonesia, and Thailand) were all of the same species. Five sensilla types housed on the antennae of female An. kochi were observed under scanning electron microscopy (SEM). In addition, this study found that An. kochi was a refractory vector, revealed by 0% susceptibility rates to infection with nocturnally subperiodic Brugia malayi. The cibarial armature was a resistant mechanism, as it killed the microfilariae in the foregut before they penetrated into the developmental site.